A chromosome-level genome assembly of the heteronomous hyperparasitoid wasp Encarsia sophia - Xiaoming Man; Cong Huang; Shengyong Wu; Jianyang Guo; Fanghao Wan; Frédéric Francis; Nianwan Yang; Wanxue Liu (Scientific Data)
Abstract Encarsia sophia, a heteronomous hyperparasitoid wasp, is a well-known biological control agent, but its genomic information is limited, hindering molecular investigations and understanding of multitrophic interactions. In this study, we present a chromosome-level genome assembly for E. sophia using Illumina, PacBio HiFi, and Hi-C technologies. The assembled genome size is 398.3 Mb, with a contig N50 of 1.0 Mb and a scaffold N50 of 74.0 Mb. The BUSCO completeness score is 97.1%, and genome coverage reaches 99.1%. Utilizing Hi-C assisted assembly, the genome was organized into five chromosomes, with a mounting rate of 95.1%. Repetitive sequences make up 54.6% of the genome, and 14,914 protein-coding genes were predicted, with 95.5% functionally annotated. The high-quality genome assembly of E. sophia is a significant achievement, marking the first complete genome for a heteronomous hyperparasitoid wasp. This milestone offers valuable insights into the evolution and host interactions of heteronomous hyperparasitoids, laying the foundation for extensive research in biological control.